2012
DOI: 10.1002/jbm.a.34345
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of cell‐binding peptides on poly‐ε‐caprolactone film surface to biomimic the peripheral nervous system

Abstract: Cell-material interactions are crucial for cell adhesion and proliferation on biomaterial surfaces. Immobilization of biomolecules leads to the formation of biomimetic substrates, improving cell response. We introduced RGD (Arg-Gly-Asp) sequences on poly-ε-caprolactone (PCL) film surfaces using thiol chemistry to enhance Schwann cell (SC) response. XPS elemental analysis indicated an estimate of 2-3% peptide functionalization on the PCL surface, comparable with carbodiimide chemistry. Contact angle was not rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 46 publications
(59 reference statements)
1
41
0
Order By: Relevance
“…The RGD motif has been proven to enhance Schwann attachment, elongation in vitro [25,26], and facilitate axon growth in the early stages across rat sciatic transaction injuries in vivo [27]. During the early phase of regeneration of peripheral nerves in the presence of RGD coated conduits, the activated Schwann cells around lesion secrete vital trophic factors, thereby providing a permissive surface and matrix molecules to support axon regeneration [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The RGD motif has been proven to enhance Schwann attachment, elongation in vitro [25,26], and facilitate axon growth in the early stages across rat sciatic transaction injuries in vivo [27]. During the early phase of regeneration of peripheral nerves in the presence of RGD coated conduits, the activated Schwann cells around lesion secrete vital trophic factors, thereby providing a permissive surface and matrix molecules to support axon regeneration [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…These molecules are selective in cell binding and can be incorporated onto neural scaffold surfaces at higher densities. Specific amino acid sequences, such as IKVAV (Ile-Lys-Val-Ala-Val), 103 YIGSR (Tyr- Ile-Gly-Ser-Arg), 104 and RGD (Arg-Gly-Asp), 105,106 have been shown to enhance the adhesion and proliferation of neural cells, and many more have been investigated for use in peripheral nerve regeneration. In a rat 15 mm nerve gap model, Itoh et al demonstrated that laminin and YIGSR peptides do not lead to different outcomes, and both improve nerve regeneration.…”
Section: Scaffold Surface Modificationsmentioning
confidence: 99%
“…SC in culture grow to confluence in 10–12 d and no more passages on the same support are allowed 38. On the other hand, this is the upper limit timing usually adopted in most papers on related investigations found in the literature on SC 39–43…”
Section: Resultsmentioning
confidence: 99%